The African Writer and the Sacred : what changes for her/him and her/his characters in the beginning of 1960 and to day ? - (:unkn) unknown (My University, 2012)
Abstract : The fight against colonial power and the will to etablish a new African State led several writers to think that the Society was the basis of the Sacred and to adopt a priest attitude, like we can see in the chapters about « National Culture » in Les damnés de la terre by Frantz Fanon, who shows a sociodicée, as Pierre Bourdieu says. But, at the end of 1960's, this conception is no more possible : books like Les soleils des indépendances by Ahmadou Kourouma denounce the African independance experience. So, Society and Sacred are two very différent notions. But the writer neither does not think that he must find a protection in the world of Art. Nor he hopes that he could be a priest or a prophet. He is adopting an other attitude : to be only a writer, and not an « African writer ». This new job is perhaps a prosaic job, not vrey different from a craftman. But it's probably a new kind of the writer consecration.
Keywords: African Research